2006
DOI: 10.1177/003172170608800324
|View full text |Cite
|
Sign up to set email alerts
|

Pay-to-Play: Fair or Foul?

Abstract: Confronted with rising costs and shrinking funding, districts have come up with the idea of charging students to participate in extracurricular activities. According to Ms. Hoff and Mr. Mitchell, there are much better ways for schools to make their programs affordable. 230 PHI DELTA KAPPAN Photo: Liquid Library I MAGINE the exhilaration as high school students throughout the country suit up for their first practice, polish their instruments, and prepare for their upcoming games and events with high-fives all a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In general, children who attend school in low-income areas consistently show the lowest academic achievement and the poorest development of social skills (Haggerty et al, 1994; Hoff & Mitchell, 2006; NCES, 2002; Pogrow, 2006; Reynolds, 1999). An examination of nationwide reading scores in 2002 revealed that fourth graders in central city schools performed lower than their peers who attended urban fringe/ large town and rural/ small town schools.…”
Section: Social-emotional Competencementioning
confidence: 99%
“…In general, children who attend school in low-income areas consistently show the lowest academic achievement and the poorest development of social skills (Haggerty et al, 1994; Hoff & Mitchell, 2006; NCES, 2002; Pogrow, 2006; Reynolds, 1999). An examination of nationwide reading scores in 2002 revealed that fourth graders in central city schools performed lower than their peers who attended urban fringe/ large town and rural/ small town schools.…”
Section: Social-emotional Competencementioning
confidence: 99%
“…Moreover, in today's reality, with public school budgets pinched and educational demands rising, in the absence of fees these activities will have to be canceled (e.g. Hoff and Mitchell, 2006;Reeves, 2006). Farkas and Duffett (2012) interviewed a representative sample of adults concerning various cost-cutting measures that district leaders are considering due to the current harsh economic situation.…”
Section: Extracurricular Activitiesmentioning
confidence: 99%